Dehydrogenation, Methyl Elimination and Insertion Reactions of the Agostic Methyl‐Bridged Complex [Mo2Cp2(μ‐κ1:η2‐CH3)(μ‐PtBu2)(μ‐CO)]. Issue 38 (30th May 2018) - Alvarez, M. Angeles; Casado‐Ruano, Melodie; García, M. Esther; García‐Vivó, Daniel; Ruiz, Miguel A.
Abstract: The high unsaturation of the title complex enabled it to react with a wide variety of molecules under mild conditions, whereby the agostic methyl ligand underwent unusual or unprecedented processes. Methane elimination occurred in the reactions with PPh2 H and SiPh2 H2, this being followed in the latter case by Si−H bond oxidative addition to give the hydride silylene derivative [Mo2 Cp2 H(μ‐P t Bu2 )(μ‐SiPh2 )(CO)]. Dehydrogenation, however, was the dominant process in the room temperature reaction with [Fe2 (CO)9 ], to give the unsaturated methylidyne cluster [Mo2 FeCp2 (μ3 ‐CH)(μ‐P t Bu2 )(CO)5 ] (Mo−Mo=2.6770(8) Å). In contrast, PMe elimination took place in the reaction with P4, to give the unsaturated triphosphorus complex [Mo2 Cp2 (μ‐η 3 :η 3 ‐P3 )(μ‐P t Bu2 )] (Mo−Mo=2.6221(3) Å). Yet a most remarkable reaction occurred with BH3 ⋅ THF, involving insertion of two BH3 units and dehydrogenation to yield [Mo2 Cp2 (μ‐B2 H4 Me)(μ‐P t Bu2 )(CO)], with the novel methyldiboranyl ligand acting as a 5‐electron donor due to the presence of two 3‐centre, 2‐electron B‐H‐Mo interactions, according to spectroscopic data and DFT calculations (Mo−Mo ca. 2.65 Å). Abstract : High unsaturation of the title compound enables the addition of very diverse p‐block molecules and transition‐metal complexes under mild conditions, whereby unusual or unprecedented transformations of the bridging methyl ligand take place, such as room‐temperature dehydrogenation, methane or methylphosphinidene elimination, and borane insertion, to give unsaturated derivatives bearing uncommon ligands.